Efficacy of a polyherbal formulation in the management of benign prostatic hyperplasia: a randomized, controlled trial - Bhat, Shabir Ahmad; Rather, Shameem Ahmad; Islam, Naquibul (International Journal of Advances in Medicine, 2021)
Background: Benign prostatic hyperplasia (BPH) affects a significant number of men beyond the age of 40 years with its incidence reaching up to 90% in 80’s. Despite multiple treatment innovations, BPH still remains a nightmare for ageing men, mostly due to its distressing lower urinary tract symptoms (LUTS) and sexual dysfunction. The severity of LUTS is graded by international prostate symptom score or American urological association symptom index (AUA-SI) along with impact on quality of life (QOL). The objective of this study was to evaluate the efficacy of an Unani polyherbal formulation, Habb-i-muqil, in improving the AUA-SI and QOL in patients with BPH. Methods:In an open, standard controlled study, 76 men, diagnosed with clinical BPH, aged between 40 and 80 years were randomly allocated for treatment for duration of 90 days with Habb-i-muqil (test drug) or Tamsulosin (standard control) after ethical approval. AUA-SI and QOL were assessed at baseline (0 day) and days 15, 30, 45, 60, 75 and 90. Results: Analysis of 60 men showed that after 90 days of treatment the percentage changes in the AUA-SI from baseline were 59.4 and 49.4% by Habb-i-muqil and tamsulosin, respectively. The test drug produced statistically significant improvement (p<0.001) in overall AUA-SI and QOL compared with standard control. Conclusions:The Unani polyherbal formulation, Habb-i-muqil, was effective in improving AUA-SI and QOL in men with BPH in comparison to tamsulosin. Both the treatments were generally well tolerated.